Separate and combined effects of advanced age and obesity on mammary adipose inflammation, immunosuppression and tumor progression in mouse models of triple negative breast cancer - Smith, Laura A.; Craven, Dalton M.; Rainey, Magdalena A.; Cozzo, Alyssa J.; Carson, Meredith S.; Glenny, Elaine M.; Sheth, Nishita; McDonell, Shannon B.; Rezeli, Erika T.; Montgomery, Stephanie A.; Bowers, Laura W.; Coleman, Michael F.; et al. (Frontiers in Oncology, 2023)
Advanced age and obesity are independent risk and progression factors for triple negative breast cancer (TNBC), which presents significant public health concerns for the aging population and its increasing burden of obesity. Due to parallels between advanced age- and obesity-related biology, particularly adipose inflammation, we hypothesized that advanced age and obesity each accelerate mammary tumor growth through convergent, and likely interactive, mechanisms. To test this hypothesis, we orthotopically transplanted murine syngeneic TNBC cells into the mammary glands of young (7 months) normoweight control, young diet-induced obese (DIO), aged normoweight control (17 months), and aged DIO female C57BL/6J mice. Here we report accelerated tumor growth in aged control and young DIO mice, compared with young controls. Transcriptional analyses revealed, with a few exceptions, overlapping patterns of mammary tumor inflammation and tumor immunosuppression in aged control mice and young DIO mice, relative to young controls. Moreover, tumors from aged control and young DIO mice, compared with young controls, had reduced abundance of cytotoxic CD8+ T cells, and depletion of CD8+ T cells in young control mice accelerated tumor growth. Finally, DIO in advanced age exacerbated mammary tumor growth, inflammation and tumor immunosuppression. These findings demonstrate commonalities in the mechanisms driving TNBC, specifically inflammation and immunosuppression, in aged and obese mice, relative to young normoweight controls, . Moreover, we found that advanced age and DIO interact to accelerate mammary tumor progression. Given the global population is getting both older and heavier, new mechanism-based intervention strategies for offsetting the separate and combined effects of age and obesity on breast cancer burden are urgently needed.